Levantamento dos recursos e capacidades utilizados pelo Núcleo de Inovação Tecnológica de uma universidade pública no processo de criação de SPIN-OFFS acadêmicas: o caso da UFMG - Gabriela D'ávila Metzker (2019)
In Brazil, Technology Transfer Offices (TTOs) are structures established by one or more Science and Technology Institutions (ICT) whose purpose is the management of the their Innovation Policies. Therefore, these offices must retain and develop resources and capabilities (routines, processes and skills) that assists in the assignments indicated in the Science and Technology Act, specially those concerning intellectual property protection and technology transfer processes, that, ultimately, collaborate to the university’s role of providing knowledge and technologies to the productive sector that can be applied in generating of new processes, products and services. One of the possible mechanisms of technology transfer is the generation of academic spin-offs, technology-based companies formed to exploit intellectual property developed at the university. Spin-offs help to improve the technologies developed at the university, collaborate to retain qualified human capital and generate revenue for universities, creating a virtuous circle of research, development and innovation. It was conducted a mapping of the resources and capacities available in a TTO that can, somehow, assist in the process of creation of academic spin-offs, considering the state of the art and the comparison with a case study, held at a federal public university. It was observed that the resources and capabilities present in the TTO studied are used in technology transfer processes as a whole, in other words, they are not specific to the academic spin-offs’ process. It was also possible to perceive the presence of ancillary institutions that act in a complementary way to the work of the office, providing some resources and capabilities indicated in the literature.